THE TRADITION OF MENRE BOLA' BARU: Reflection of Pancasila Values in Realizing Interfaith Harmony in Bugis Soppeng Society - Ghina Mufidha,; Andi Agung Mallongi,; Aulia Rahmadani,; Muhammad Aqso Che Athoriq. R, (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT This study examines the tradition of the Bugis community in Soppeng Regency as a representation of Pancasila values in strengthening inter-religious harmony in the midst of Indonesia's multicultural society. The main purpose of this study is to analyze the philosophical meaning in the tradition and examine its relationship with the precepts of Pancasila, especially the First Precept (The One Godhead), the Third Precept (Indonesian Unity), and the Fifth Precept (Social Justice for All Indonesian People). This study uses a qualitative approach. The methods used included field observations, structured interviews with community leaders, and documentation analysis. The results of the study show that Menre' Bola Baru is not just a procession of moving houses, but a cultural ritual full of religiosity, mutual cooperation, and inclusive participation. Elements such as the reading of Barzanji, the Mappasili ceremony, and eating together strengthen social and spiritual solidarity between citizens, despite differences in status and beliefs. This tradition reflects the practice of Pancasila in a concrete way through togetherness, justice, and respect for diversity. Therefore, recommended preservation strategies include integration into education, revitalization through cultural tourism, government policy support, and the use of digital media. In conclusion, Menre' Bola Baru is an essential cultural heritage in strengthening national ideology and social cohesion, so synergy is needed between the community, educational institutions, and policy makers to maintain its existence in the modern era. ABSTRAK Penelitian ini mengkaji tradisi Menre’ Bola Baru masyarakat Bugis di Kabupaten Soppeng sebagai representasi nilai-nilai Pancasila dalam memperkuat kerukunan antarumat beragama di tengah masyarakat multikultural Indonesia. Tujuan utama dari studi ini adalah menganalisis makna filosofis dalam tradisi tersebut serta menelaah keterkaitannya dengan sila-sila Pancasila, khususnya Sila Pertama (Ketuhanan Yang Maha Esa), Sila Ketiga (Persatuan Indonesia), dan Sila Kelima (Keadilan Sosial bagi Seluruh Rakyat Indonesia). Penelitian ini menggunakan pendekatan kualitatif . Metode yang digunakan meliputi observasi lapangan, wawancara terstruktur dengan tokoh masyarakat, dan analisis dokumentasi. Hasil penelitian menunjukkan bahwa Menre’ Bola Baru bukan sekadar prosesi pindah rumah, melainkan sebuah ritual budaya yang sarat nilai religiusitas, gotong royong, dan partisipasi inklusif. Unsur-unsur seperti pembacaan Barzanji, upacara Mappasili, serta makan bersama memperkuat solidaritas sosial dan spiritual antarwarga, meski memiliki perbedaan status maupun keyakinan. Tradisi ini mencerminkan pengamalan Pancasila secara konkret melalui kebersamaan, keadilan, dan penghargaan atas keragaman. Oleh karena itu, strategi pelestarian yang direkomendasikan meliputi integrasi ke dalam pendidikan, revitalisasi melalui pariwisata budaya, dukungan kebijakan pemerintah, serta pemanfaatan media digital. Kesimpulannya, Menre’ Bola Baru merupakan warisan budaya yang esensial dalam memperkuat ideologi kebangsaan dan kohesi sosial, sehingga diperlukan sinergi antara masyarakat, lembaga pendidikan, dan pemangku kebijakan untuk menjaga eksistensinya di era modern.